Technological properties and selected safety aspects of different cuts of organic and conventional pork. (7th July 2021) - Latoch, Agnieszka; Wójciak, Karolina M.; Popek, Stanisław; Rohn, Sascha; Halagarda, Michał
Summary: The present study aimed at evaluating and comparing technological quality and selected safety aspects of commercial organic and conventional pork cuts. The technological value was determined on the basis of pH value, centrifugation loss, cooking loss, drip loss, colour parameters (as measured with L * a * b * system), total heme pigments and total heme iron. The meat safety was verified based on the content of nitrate, nitrite, cadmium, lead, total microbial count, number of Listeria monocytogenes and Salmonella . The results indicated that organic meat had higher content of heme pigments and heme iron than conventional meat. The rearing system had no effect on the lightness. The organic loins and shoulders were redder and yellower than conventional ones. Neither organic nor conventional meat cuts were contaminated by pathogenic bacteria and nitrite/nitrate residues. Legal requirements concerning cadmium content were met for all the tested samples, whereas concerning lead only for organic loins. Abstract : Organic and conventional equivalents ofpork meat cuts have similar technological value. Neverthless, organic meat has higher content of heme pigments and heme iron than conventional meat.